Economic Evaluation of the MEDENOX Trial: A Canadian Perspective - André Lamy; Xiaoyin Wang; Rosanne Kent; Kelly M Smith; Amiram Gafni (Canadian Respiratory Journal)
OBJECTIVE: To perform an economic evaluation of the Prophylaxis in Medical Patients with Enoxaparin (MEDENOX) trial from a Canadian perspective.